A magnetic soft robot with rolling and grasping capabilities. (April 2023) - Wang, Xiaodong; Bo, Zhihui; Guo, Canzhi; Wu, Jiaoyi; Liu, Youwen; Sun, Wan
Soft robots offer a great application potential in the field of military, medical, and industry. In this study, a rolling gait was adopted to the design of the soft robot so as to improve the locomotion velocity of the soft robot actuated by the magnetic field. The soft robot was fabricated as a square frame structure (6 × 6 × 0.6 mm) to achieve grasping function. The experimental results indicated that the designed soft robot could roll on a slope with a maximum inclination around 30° under the given conditions. The velocity of the soft robot during the rolling process would decrease with the increase of the inclination. Meanwhile, the soft robot could carry objects 3.75 times its own weight when it rolled on a level pavement. Further analysis and experiments suggested that the rolling locomotion of the soft robot relied on the magnetic torque and the friction force. The locomotion velocity of the soft robot was related to the perimeter of the contour composed of the soft robot and the object being grasped. Moreover, a modular assembly strategy was proposed to improve the locomotion and grasping performance of the soft robot. The findings of this work will help to promote the application of untethered soft robots.